Rancang Bangun Sistem Pendeteksian Penyakit Tanaman Anthurium Dengan Metode Variable-Centered Intellegent Rule System (VCIRS) - Saputra, Ade Candra; Parhusip, Jadiaman; Hidayat, Yusup (Journal of Information Technology and Computer Science, 2021)
The anthurium plant disease detection system that has been built is a system that can help diagnose diseases in anthurium plants based on symptoms input by the user and provide solutions to these problems. This system is intended to provide easy access to information about the types of anthurium diseases and their treatment solutions for planters, anthurium enthusiasts, or nonexpert who really need this information. This system uses disease and treatment data sourced from anthurium plant experts. There are 13 diseases and 44 symptoms of disease which becomes the system knowledge base. The research methodology carried out includes the process of knowledge acquisition, knowledge representation, VCIRS design, system analysis and design, system implementation and testing. In this study, the anthurium plant detection system was tested 13 times. The trial results showed that the system was able to diagnose anthurium plant diseases with an accuracy rate of 92.3%. Errors occur because of the diagnosis of symptoms used in several diseases and it turns out to have a higher usage rate value in a VCIRS rule.